A RANDOMIZED CONTROL STUDY TO EVALUATE THE ROLE OF HERBAL IMMUNOMODULATORS IN BOOSTING THE IMMUNITY AND OVERALL HEALTH OF HEALTHCARE WORKERS IN COVID-19 WARDS: AN EXPLORATORY, FEEDBACK CLINICAL STUDY - CR, JAYANTHI; HR, AVINASH; SRIDHAR, SWETHA; K, AKHILA; SRIDHAR, SRIYA; KUMAWAT, RAJESH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to evaluate the role of the herbal immunomodulators Immusante and Guduchi in boosting the immunity and overall health of healthcare workers assigned to coronavirus disease 2019 (COVID-19) wards. Methods: An open-label, randomized, prospective, and single center clinical study was conducted among 100 healthcare workers assigned to COVID-19 wards. Eligible subjects (50 in each arm) were randomly assigned to either arm I (Immusante+Guduchi tablets) or arm II (treatment as per the institutional policy). Assessments after 30 days of treatment included respiratory symptoms, Adapted Immune Status Questionnaire (ISQ), improvement in quality of life (Short form 12 [SF-12] Health Survey), and safety and tolerability. Results: All 100 subjects completed the study as per the protocol. There were no respiratory symptoms in the subjects in arm 1. However, four subjects (8%) in arm II reported cough during the study period. A better Immune status improvement was seen through the adapted ISQ in arm I as compared to arm II. In each of the 8 SF-12 Health Survey domains, a statistically significant difference was observed in arm I compared to arm II. A retrospective assessment of COVID-19 infection showed only 8% of subjects as COVID-19 positive in arm I compared with 26% of subjects in arm II. Conclusion: Considering the positive trend observed in this study in terms of ISQ, SF-12, and COVID-19 infection rates, the combination of Immusante and Guduchi in healthcare workers at a high risk of contracting COVID-19 infection had a beneficial effect in boosting immunity and overall health.